Dynamic changes in the relationship of microglia to cardiovascular neurons in response to increases and decreases in blood pressure. (4th August 2016) - Kapoor, Komal; Bhandare, Amol M.; Nedoboy, Polina E.; Mohammed, Suja; Farnham, Melissa M.J.; Pilowsky, Paul M.
Highlights: Microglia alter spatial distribution in response to changes in blood pressure. Increased blood pressure causes microglia to contact more synapses. Decreased blood pressure reduces microglial contact with synapses. Abstract: Microglia are present throughout the central nervous system (CNS) and express receptors for every known neurotransmitter. During inflammation, microglia change into a state that either promotes removal of debris (M1), or into a state that promotes soothing (M2). Caudal- and rostral- ventrolateral medullary regions (CVLM and RVLM, respectively) of the brainstem are key nuclei involved in all aspects of the cardiovascular system. In this study, we investigate a novel role for microglia in cardiovascular control in the brainstem of adult male Sprague–Dawley (SD) rat. Here we show, that increases and decreases in blood pressure (BP) triggers alertness in the physiology of microglia in the brainstem region; inducing changes in microglial spatial distribution and the number of synapses in contact with microglial end processes. Following 6 h of acute hypertension, the number of synapses in contact with microglia increased by ≈30% in both regions of the brainstem, CVLM and RVLM. Induction of acute hypotension for 6 h causes microglia to reduce the number of synaptic contacts by >20% in both, CVLM and RVLM, nuclei of the brainstem. Our analysis of the morphological characteristics of microglia, and expression levels of M1 and M2, reveals that the changes induced in microglial behavior do not require any obvious dramatic changes in their morphology. Taken together, our findings suggest that microglia play a novel, unexpected, physiological role in the uninjured autonomic nuclei of CNS; we therefore speculate that microglia act cooperatively with brainstem cardiovascular neurons to maintain them in a physiologically receptive state.